Atypical presentation of thyroglossal cyst in pediatric patient: a case report - Narang, Ekta; Tyagi, Sonali; Jain, Neha; Singh, Jyoti (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Thyroglossal duct cysts are the most common cause of congenital neck swelling that may present at any age. Classically, it presents as an anterior midline neck swelling that moves with protrusion of the tongue. The usual treatment of choice is Sistrunk operation. It can have atypical presentation requiring a thorough preoperative assessment before intervention. Here we discussed a case of atypical presentation of thyroglossal duct cyst in a 4 year old child.